Penegakan Hukum terhadap Anak sebagai Korban Tindak Pidana Pornografi Dalam Lingkup Keluarga - Suryani, Wami Irma; Gettari, Trie Rahmi (Program Studi Hukum Keluarga Islam STAIN Mandailing Natal, 2025)
This article aims to examine the extent to which legal enforcement mechanisms protect children who are victims of pornographic crimes within the family context. It highlights the gaps in current legal responses to intra-familial pornography-related offenses involving minors and proposes a child-sensitive legal model to address these challenges. Such offenses become particularly complex when they occur within the family structure, as they involve intricate power dynamics, emotional bonds, and legal relationships. The article analyzes the enforcement of laws concerning children as victims of pornography-related crimes within familial settings. This study employs a normative juridical method with a statute and case study approach. The findings reveal that, despite the existence of a robust legal framework, the enforcement of laws against perpetrators who disseminate pornographic content still faces significant challenges—ranging from legal and technological constraints to cultural attitudes within society. Accordingly, enhanced synergy among law enforcement agencies, state institutions, and civil society is crucial in fostering a safe and healthy digital environment, especially for children who are vulnerable to such crimes.